PERSEPSI PELAKU BISNIS SPBU DI KABUPATEN KUDUS TERHADAP ETIKA BISNIS ISLAM - Hakim, M Arif (STAIN Salatiga, 2013)
This research aims to (1) examine empirically the relationship between ethics system options with urgency ethics in business, and (2) empirically examine differences in perceptions of gas stations businessmen in the district Kudus on the relationship between ethics and business.While the benefits are (1) to provide empirical evidence of the differences in perceptions of gas stations businessmen in the district Kudus on the relationship between ethics and business, and (2) to contribute ideas for gas stations businessmen in the district Kudus in conducting business activities and strategies.Based on the discussion in this research it can be concluded that (1) there is a very strong relationship, direct and significant between these two variables, ethics system options with urgency ethics in business; (2) there was no significant difference between the perceptions of gas stations businessmen in the district Kudus on the relationship between ethics and business.